Systemic Inflammatory Response and Serum Lipopolysaccharide Levels Predict Multiple Organ Failure and Death in Alcoholic Hepatitis - Michelena, Javier (Hepatology, 2015)
Alcoholic hepatitis (AH) frequently progresses to multiple organ failure (MOF) and death. However, the driving factors are largely unknown. At admission, patients with AH often show criteria of systemic inflammatory response syndrome (SIRS) even in the absence of an infection. We hypothesize that the presence of SIRS may predispose to MOF and death. To test this hypothesis, we studied a cohort including 162 patients with biopsy-proven AH. The presence of SIRS and infections was assessed in all patients, and multivariate analyses identified variables independently associated with MOF and 90-day mortality. At admission, 32 (19.8%) patients were diagnosed with a bacterial infection, while 75 (46.3%) fulfilled SIRS criteria; 58 patients (35.8%) developed MOF during hospitalization. Short-term mortality was significantly higher among patients who developed MOF (62.1% versus 3.8%, P <0.001). The presence of SIRS was a major predictor of MOF (odds ratio = 2.69, P=0.025) and strongly correlated with mortality. Importantly, the course of patients with SIRS with and without infection was similar in terms of MOF development and short-term mortality. Finally, we sought to identify serum markers that differentiate SIRS with and without infection. We studied serum levels of high-sensitivity C-reactive protein, procalcitonin, and lipopolysaccharide at admission. All of them predicted mortality. Procalcitonin, but not high-sensitivity C-reactive protein, serum levels identified those patients with SIRS and infection. Lipopolysaccharide serum levels predicted MOF and the response to prednisolone. CONCLUSION: In the presence or absence of infections, SIRS is a major determinant of MOF and mortality in AH, and the mechanisms involved in the development of SIRS should be investigated; procalcitonin serum levels can help to identify patients with infection, and lipopolysaccharide levels may help to predict mortality and the response to steroids.